Pluralistic Legal Systems and Martial Rape: Cross-National Considerations - Venkatesh, Vasanthi (The Right to Say No: Marital Rape and Law Reform in Canada, Ghana, Kenya and Malawi, 2017)
This chapter focuses on political issues that arise when claims for gender justice, such as the call for criminalising marital rape, are made in societies or states with pluralistic legal systems, especially with customary and Indigenous law systems.
Keywords: Vasanthi Venkatesh